2020
DOI: 10.1111/tpj.14671
|View full text |Cite
|
Sign up to set email alerts
|

Wide‐ranging transcriptome remodelling mediated by alternative polyadenylation in response to abiotic stresses in Sorghum

Abstract: Alternative polyadenylation (APA) regulates diverse developmental and physiological processes through its effects on gene expression, mRNA stability, translatability, and transport. Sorghum is a major cereal crop in the world and, despite its importance, not much is known about the role of post-transcriptional regulation in mediating responses to abiotic stresses in Sorghum. A genome-wide APA analysis unveiled widespread occurrence of APA in Sorghum in response to drought, heat, and salt stress. Abiotic stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 91 publications
(117 reference statements)
2
30
0
Order By: Relevance
“…First, our interest was to investigate rapid changes in gene expression in response to drought stress. Second, we and others have previously shown that drought marker genes are induced within 1 to 6 h [32,37] Two biological replicates were analyzed for each condition resulting in 32 samples (4 genotypes × 2 conditions × 2 time points × 2 replicates). The correlation coefficient between biological replicates was high (R 2 = 0.87-0.99) supporting the reproducibility of the results.…”
Section: Transcriptome Analysis Of Two Drought-resistant and Two Droumentioning
confidence: 99%
“…First, our interest was to investigate rapid changes in gene expression in response to drought stress. Second, we and others have previously shown that drought marker genes are induced within 1 to 6 h [32,37] Two biological replicates were analyzed for each condition resulting in 32 samples (4 genotypes × 2 conditions × 2 time points × 2 replicates). The correlation coefficient between biological replicates was high (R 2 = 0.87-0.99) supporting the reproducibility of the results.…”
Section: Transcriptome Analysis Of Two Drought-resistant and Two Droumentioning
confidence: 99%
“…In Arabidopsis, the "AAAAAA" is not identified from the comparable region, and CE is usually rich in Ts [28]. Interestingly, in a recent study of sorghum, the hexamer "AAAAAA" has been revealed prominently in PACs from both 3'UTR and intron at the same region; and heat, salt and drought stresses do not affect the enrichment [17]. These results indicate that the heat stress could induce the usage of specific sequence signals to confer unique APA-mediated transcripts.…”
Section: Discussionmentioning
confidence: 97%
“…5'UTR and protein-coding) polyA sites, which suggested a negative role of gene regulation [15]. In addition, genomewide profiling of APA in sorghum has shown that some stress-induced isoforms were associated with a unique intronic polyA signal [17]. These results indicate that global shift of polyA site in response of stress is a strategy of survival which affect a wide-range of gene functions.…”
Section: Introductionmentioning
confidence: 95%
“…In Arabidopsis, the "AAAAAA" is not identi ed from the comparable region, and CE is usually rich in Ts [28]. Interestingly, in a recent study of sorghum, the hexamer "AAAAAA" has been revealed prominently in PACs from both 3'UTR and intron at the same region; and heat, salt and drought stresses do not affect the enrichment [17]. These results indicate that the heat stress could induce the usage of speci c sequence signals to confer unique APA-mediated transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…5'UTR and protein-coding) polyA sites, which suggested a negative role of gene regulation [15]. In addition, genome-wide pro ling of APA in sorghum has shown that some stress-induced isoforms were associated with a unique intronic polyA signal [17]. These results indicate that global shift of polyA site in response of stress is a strategy of survival which affect a wide-range of gene functions.…”
Section: Introductionmentioning
confidence: 94%